2014
DOI: 10.37190/epe140305
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and COD removal from chemically and electrochemically coagulated wastewater

Abstract: Wastewater coagulation and electrocoagulation were investigated as sorption processes involving colloidal sorbents such as (Al(OH) 3) n , (Fe(OH) 3) m and (Fe(OH) 2) p. An attempt was made to fit experimental data to two popular sorption models. Based on a statistical and mathematical analysis of the obtained results, the Langmuir model of chemical adsorption was regarded more probable than the Freundlich model. The highest maximum adsorption of phosphorus in the analyzed wastewater was achieved with the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…OHions compete with PO 4 3for Fe 3+ ions and, at the same time, sorption processes can proceed (Li et al 2009). Smoczyński et al (2014) found that the main mechanism of phosphorus removal in the chemical and electrochemical coagulation processes is the chemical sorption process (chemisorption); as a result, covalent bonds are formed between the adsorbate particles and the adsorbent -hydrolysed metal species surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OHions compete with PO 4 3for Fe 3+ ions and, at the same time, sorption processes can proceed (Li et al 2009). Smoczyński et al (2014) found that the main mechanism of phosphorus removal in the chemical and electrochemical coagulation processes is the chemical sorption process (chemisorption); as a result, covalent bonds are formed between the adsorbate particles and the adsorbent -hydrolysed metal species surface.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible to obtain the assumed permissible concentrations for phosphorus in wastewater discharged from wastewater treatment plant after applying either biological dephosphatation or chemical precipitation methods using coagulants, i.e., aluminium or iron(III) salts (Gu et al 2011;Zou and Wang 2017). Chemical coagulation is also initiated by the dissolution of metals in the electrocoagulation process after an electric current was applied to the electrodes (Smoczyński et al 2014). A source of metals in the solution may also be a galvanic cell built of electrodes of steel (anode) and carbon (cathode), immersed in an electrolyte (Yuan et al 2009).…”
Section: Introductionmentioning
confidence: 99%